2006
DOI: 10.1143/jjap.45.3669
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Ozone Detection Using Single-Walled Carbon Nanotube Networks

Abstract: We demonstrated ultrasensitive detection of ozone using single-walled carbon nanotube (SWNT) networks directly grown on a conventional sensor substrate. Ozone was detected down to the ppb level (∼6 ppb) at room-temperature operation with a fast response. Using an electrical breakdown technique, gas sensitivity was improved. This result clearly indicates that owing to its high sensitivity, simplicity in fabrication and compact size, an SWNT sensor provides a feasible route to ultrasensitive ozone detection surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…For individual, pristine single-walled carbon nanotubes, calculations and experiments have shown that the interactions with other gases present in the atmosphere, such as N 2 , H 2 , CO, H 2 O and CO 2 are negligible [ 19 ]. However, nanotubes are sensitive to other interfering pollutants, such as SO 2 [ 20 ], NH 3 [ 12 ] and O 3 [ 21 ]. Therefore, the task of enhancing the selectivity of SWNT sensors to NO 2 must also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…For individual, pristine single-walled carbon nanotubes, calculations and experiments have shown that the interactions with other gases present in the atmosphere, such as N 2 , H 2 , CO, H 2 O and CO 2 are negligible [ 19 ]. However, nanotubes are sensitive to other interfering pollutants, such as SO 2 [ 20 ], NH 3 [ 12 ] and O 3 [ 21 ]. Therefore, the task of enhancing the selectivity of SWNT sensors to NO 2 must also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…A long recovery time for ammonia vapor was often reported using SWCNT based sensors [19,29]. Heating, UV illumination and high vacuum operations were often performed to speed up the recovery process of SWCNT sensors [29][30][31]. The above processes are not applicable in the paper-based sensors.…”
Section: Page 8 Of 39mentioning
confidence: 99%
“…5 25-26 Therefore, processing of CNTs bundle with the ozone [27][28][29] or nitrogen dioxide 9 was considered as possible ways to improve the electrical property of CNT yarns and sheets. However, the ozone irradiation process creates large induced defects at the CNTs surface.…”
Section: Communicationmentioning
confidence: 99%
“…Figure 2 been reported that the ozone irradiation decreases the resistance of CNTs, which is a simple approach for the CNTs oxidation. [27][28][29] The CNTs have p-type conductivity and gain holes due to charge transfer between CNTs and the adsorbed ozone molecules with the ozone irradiation, thereby reducing the resistance of CNTs. However, the ozone irradiation on the CNTs causes not only the hole injection but also the induction of defects at the same time.…”
Section: Figures 2(a) and (B)mentioning
confidence: 99%